P128 Depression, anxiety and stress among Inflammatory Bowel Disease patients during COVID-19: A UK cohort study. (27th May 2021) - Luber, R; Duff, A; Pavlidis, P; Honap, S; Meade, S; Ray, S; Anderson, S; Mawdsley, J; Samaan, M; Irving, P
Abstract: Background: Patients with chronic diseases, particularly those requiring immunosuppression, are thought to be at increased risk of poor mental health during the COVID-19 pandemic. However, few studies have assessed the mental health of such patients during the current or past pandemics. We aimed to assess the incidence of depression, anxiety & stress in a cohort of inflammatory bowel disease (IBD) patients early during the COVID-19 pandemic, & explore for association with risk of severe COVID-19 based on British Society of Gastroenterology guidelines, & other factors. Methods: A survey including the Patient Health Questionnaire-9, General Anxiety Disorder-7, & Perceived Stress Scale tools for depression, anxiety & stress, respectively, was administered to a cohort of IBD patients from a tertiary centre in London, United Kingdom, in June 2020. Results: 274 patients responded to the survey (57% response rate), including 54 low risk, 152 moderate risk, & 68 high risk for severe COVID-19. Moderate-severe depression was observed in 61 (22.5%), moderate-severe anxiety in 49 (18%), while 39 (14%) had both diagnoses (Table). Mean (SD) stress score was 16.2 (7.4). There was no association between degree of severe COVID-19 risk & psychological morbidity. Flare symptoms & fatigue were associated with worse psychological morbidity across all measures, while accessibility of information regarding COVID-19 risk & reducing that risk was protective for depression (OR 0.56 [0.33–0.94], p=0.03), anxiety (OR 0.62 [0.4–0.96], p=0.03), & stress (standardized β-coefficient -0.15 [-0.28- - 0.03], p=0.02) (Figure). 79 (30%) respondents were interested in receiving psychological support during the pandemic, while 200 (76%) expressed interest beyond the pandemic. Conclusion: Depression, anxiety & stress among IBD patients during the pandemic are common, however their frequency is similar to pre-pandemic rates & general population levels reported during the same period. Ensuring easy access to personalized risk information with targeted psychological support may mitigate psychological burden as patients reintegrate into society & deal with future COVID-19 waves or variants.